Diagnostic evaluation of RNA sequencing for the detection of genetic abnormalities associated with Ph-like acute lymphoblastic leukemia (ALL). Issue 4 (3rd April 2017) - Yap, Kai Lee; Furtado, Larissa V.; Kiyotani, Kazuma; Curran, Emily; Stock, Wendy; McNeer, Jennifer L.; Kadri, Sabah; Segal, Jeremy P.; Nakamura, Yusuke; Le Beau, Michelle M.; Gurbuxani, Sandeep; Raca, Gordana
Abstract: Philadelphia (Ph)-like acute lymphoblastic leukemia (ALL) is a molecular subtype of high-risk B-cell ALL characterized by formation of abnormal gene fusions involving tyrosine kinase (TK) and cytokine receptor genes and activation of TK signaling. Because of the diversity of associated genetic changes, the detection of Ph-like ALL cases currently requires multiple cytogenetic and molecular assays; thus, our goal was to develop a consolidated workflow for detecting genetic abnormalities in Ph-like ALL. We found that total and targeted RNA sequencing (RNAseq)-based approach allowed the detection of abnormal fusion transcripts ( EBF1-PDGFRB, P2RY8-CRLF2, RCSD1-ABL1, and RCSD1-ABL2 ). The bioinformatics algorithm accurately detected the fusion transcripts without prior input about possible events. Additionally, we showed that RNAseq analysis enabled evaluation for disease-associated sequence variants in expressed transcripts. While total RNAseq can be a second tier approach allowing discovery of novel genetic alterations, the targeted RNAseq workflow offers a clinically applicable method for the detection of fusion transcripts.